Analisis Hambatan Dalam Perkuliahan E-Learning Berbasis Android Di Prodi Tadris Matematika Pada Pandemi Covid-19 - Patri Ayu; Fevi Rahmadeni; Mutia (Program Studi Pendidikan Matematika FIP UNHASY, 2021)
The purpose of the study was to determine the process, obstacles (internal and external) and efforts to overcome obstacles to android-based E-Learning lectures in the TMM Study Program during the Covid-19 pandemic. This type of descriptive qualitative research. Data collection technique; Observation, interview and documentation. The research subjects were lecturers and students (16 people) who took the Differential Calculus course. Data analysis techniques: data reduction, data presentation and conclusion drawing. The results showed that the E-Learning lecture process used the WhatsApp Group and Google Classroom applications. Barriers to E-Learning lectures, namely, internal factors (1) student health conditions. (2) learning equipment or learning media that are incomplete. Barriers from external factors, (1) the implementation time of the learning process that is less disciplined. (2) the surrounding environment is not conducive. (3) students' motivation and interest in learning are lacking because lectures are individual. Efforts to overcome obstacles to E-Learning lectures, namely: quota assistance from the government; Lectures using Zoom and Google Meet; The internet network is evenly distributed in every area; Increase self-motivation and interest; Presentation of concise material in the form of video; Discipline in college time; using web-based E-Learning; based learning; The assignment is in the form of making videos to practice creativity and presentations to see student activity and creativity.